PENGELOLAAN PEMBELAJARAN ILMU PENGETAHUAN ALAM PADA SEKOLAH UNGGULAN DI SMP NEGERI 1 PURWODADI - DUMININGSIH , DUMININGSIH (2011)
Research purposes are (1) Describing characteristics of science learning materials management in 1 Government Junior High School Purwodadi. (2) Describing characteristics of science learning interaction management in 1 Government Junior High School Purwodadi. (3) Describing characteristics of science learning evaluation management in 1 Government Junior High School Purwodadi. Research mode is qualitative research, with etnography design. It has been done in 1 Government Junior High School Purwodadi Grobogan District. Research informants are headmaster, vice principle of curriculum, teachers, dan students. Collecting data technique is done by using depth interview, participation observation and documentation. Data analysis in this research is using managed site data analysis method to describe. Data legality test uses data credibility, by step continuous observation, triangulation of data and discuss with others. Research results are: (1) Science learning material management in 1 Government Junior High School Purwodadi, has done based on headmaster education calender based on even term program and odd term program, science learning material including basic competence and time allocation for each basic competences distributed to efective weeks in each terms as an application of Learning Execution Planning (RPP) managed by subject teacher conference. Science Learning material has been managed based on KTSP. (2) Learning interaction which has done by science teacher including begin activity; content activity; and closing activity. Beginning learning activity purpose to student having preparing to join learning process. Content activity inlearning, teacher focus on student learning experience form process. Closing activity as a student study result assesing and continuity process. (3) Science learning evaluation has done by teacher after managed curriculum component including learning material, education media and learning method, prepared and executed in a right way and accurate. Learning evaluation purposes to get information about student learning progress based on basic standard and basic competence in using techique: work assesment, attitude assessment, written assessment, project assessment, product assessment, portofolio using, and self assessment. Science learning evaluation has done by teacher each twice meeting, in oral,written, assingment and presentation.